Radiation induced sarcoma: a risk that is almost forgotten. - Ruhi Fadzlyana J; Nani Harlina ML; Saladina Jaszle J; Rohaizak M (Department of Surgery, UKM Medical Centre, 2014)
Radiotherapy has been widely use as an adjuvant therapy in the breast cancer management. The usage has increased the incidence of radiation induce sarcoma. We here present a case of radiation induce sarcoma of the axilla following mastectomy and axillary lymph node dissection for infiltrating ductal carcinoma.